Low‐carbon optimal scheduling strategy for multi‐agent integrated energy system of the park based on Stackelberg–Nash game - Yanbo Chen; Jiaqi Li; Zhe Fang; Ning Zhang; Tao Huang; Zuomao Chen (IET Energy Systems Integration, 2024)
Abstract Under the background of achieving the dual‐carbon goal, the park is a natural experimental field for practicing the dual‐carbon goal. A low‐carbon optimal scheduling strategy for a multi‐agent park‐integrated energy system (P‐IES) based on the Stackelberg–Nash game is proposed. Firstly, a low‐carbon P‐IES scheduling model is established, considering the two‐stage operation of power‐to‐gas (P2G) technology and reward–punishment stepwise carbon trading mechanism. Then, a two‐layer game optimisation model is proposed with a park‐integrated energy system operator (P‐IESO) as the leader and multiple low‐carbon P‐IESs as followers. Among them, the parks are connected with each other through the power trading channels. Then, the Nash equilibrium solution is obtained by the iterative search method, and the uniqueness of the equilibrium solution of the game is proven, so as to determine the optimal pricing strategy of the operator. Finally, a typical industrial park is taken as an example for simulation verification. The example analysis verifies that the model can effectively reduce the system's carbon emissions and improve the park's economic benefits and low‐carbon levels, thereby achieving the coordinated development of low‐carbon and economic performance in the park.